That neighbor kid - Miyares, Daniel (Simon & Schuster Books for Young Readers, 2017)
In this nearly wordless picture book, a young girl spies on her new neighbor, a young boy who is building something from planks of the fence between their backyards
Keywords: Neighbors; Friendship; Tree houses; Baumhaus; Freundschaft; Nachbar; Bilderbuch